The control of transcriptional memory by stable mitotic bookmarking - Maëlle Bellec; Jérémy Dufourt; George Hunt; Hélène Lenden-Hasse; Antonio Trullo; Amal Zine El Aabidine; Marie Lamarque; Marissa M Gaskill; Héloïse Faure-Gautron; Mattias Mannervik; Melissa M. Harrison; Jean‐Christophe Andrau; et al. (2022)
Abstract To maintain cellular identities during development, gene expression profiles must be faithfully propagated through cell generations. The reestablishment of gene expression patterns upon mitotic exit is mediated, in part, by transcription factors (TF) mitotic bookmarking. However, the mechanisms and functions of TF mitotic bookmarking during early embryogenesis remain poorly understood. In this study, taking advantage of the naturally synchronized mitoses of Drosophila early embryos, we provide evidence that GAGA pioneer factor (GAF) acts as a stable mitotic bookmarker during zygotic genome activation. We show that, during mitosis, GAF remains associated to a large fraction of its interphase targets, including at cis -regulatory sequences of key developmental genes with both active and repressive chromatin signatures. GAF mitotic targets are globally accessible during mitosis and are bookmarked via histone acetylation (H4K8ac). By monitoring the kinetics of transcriptional activation in living embryos, we report that GAF binding establishes competence for rapid activation upon mitotic exit.